Mitigation Measures for Significant Factors Instigating Cost Overrun in Highway Projects - Samiullah Sohu; Abd Halid Bin Abdullah; Bashir Ahmed Memon; Sasitharan Nagapan; Nadeem Ul Kareem Bhatti (Salehan Institute of Higher Education, 2018)
Construction industry has created numerous employment opportunities and playing a role model in economic growth of Pakistan. This industry is facing serious and critical problem of cost overrun especially in highway sector in country Pakistan particularly in Sindh Province. The purpose of this study is to identify mitigation measures for significant factors of cost overrun in highway projects of Sindh Province. In this study, mixed-mode research approach has been used. Quantitatively, a structured questionnaire based on 64 common factors of cost overrun from in-depth literature review was developed and distributed to30 selected respondents among the client, contractor and consultant having more than 15 years of experience in handling highway projects in Sindh Province. The collected data was statistically analyzed using SPSS where 8 most significant factors of cost overrun were identified. Qualitatively, the identified eight most significant factors were then incorporated in open ended questionnaire and distributed to 30 selected experts for them to write possible mitigation measures for each of the significant factors. The data was then analyzed through content analysis technique to rank the mitigation measures according to their substantiality. The results of this study would be helpful for construction practitioners to be used as reference in taking up appropriate measures in controlling cost overrun in highways projects in Pakistan.